Reaksi Pasar Atas Dividend Initiation dan Dividend Omission - Adi Pertiwi, Ni Putu; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p13, 2019)
Dividend initiation and dividend omission announcements are policies that can influence investor decisions in investing. Dividend changes can be a signal about the company’s performance in the future. The purpose of this study is to analyze at market reactions to dividend initiation and dividend omission. This research was conducted on the Indonesia Stock Exchange with a research period of 10 years, from 2008 to 2017. The research sample were 91 companies for dividend initiation and 80 companies for dividend omission. Samples are determined by purposive sampling method. The results ofthe one sample t-test show that the market reacts negatively to dividend omission, but there is no reaction to dividend initiation. Keywords: Dividend initiation, dividend omission, market reaction